Experiences of support garments following bowel stoma formation: analysis of free-text responses in a cross-sectional survey - Gill Hubbard; Claire Taylor; Julie Munro; Nicola Dames; William Goodman; Raymond Oliphant; Rebecca Beeken (BMJ Open Gastroenterology, 2019)
AimTo explore the experiences of support garments when adjusting to bodily change following bowel stoma formation.DesignThematic analyses of free-text responses in a cross-sectional survey of the stoma population in 2018.MethodsFree-text responses were invited so that respondents could describe their experiences in more detail. A process of induction was chosen to allow for themes to emerge directly from the data. The concept ‘embodiment’ was used as a theoretical framework during interpretation.Results1425 people with a bowel stoma responded to the survey, of whom 598 provided free-text responses. Four themes about experiences of support garments in the context of changed bodily experiences following stoma formation were identified: body complications, which is about experiences of using support garments to prevent or self-manage parastomal hernia; body appearance, which is about hiding the stoma and stoma appliance; body function, which is about managing stoma appliance complications; and body sensation, which is mainly about negative experiences of ill-fitting garments.ConclusionSupport garments can be understood as items that are used by people during an ongoing process of adjusting to bodily changes following stoma formation and as part of an ongoing process of reconstructing new embodied selves.ImpactThis is the first study to explore people’s experiences of support garments following bowel stoma formation. Support garments are used in the self-management of body complications, appearance, function and sensations. Stoma nurses may draw on the findings of this study to advise patients about the benefits of garments for adjusting to bodily change, and garment suppliers should address people’s negative experiences by improving garments.